Dazzle Camouflage Affects Speed Perception - Scott-Samuel, Nicholas E.; Baddeley, Roland; Palmer, Chloe E.; Cuthill, Innes C. (PLOS ONE, 2011)
Movement is the enemy of camouflage: most attempts at concealment are disrupted by motion of the target. Faced with this problem, navies in both World Wars in the twentieth century painted their warships with high contrast geometric patterns: so-called “dazzle camouflage”. Rather than attempting to hide individual units, it was claimed that this patterning would disrupt the perception of their range, heading, size, shape and speed, and hence reduce losses from, in particular, torpedo attacks by submarines. Similar arguments had been advanced earlier for biological camouflage. Whilst there are good reasons to believe that most of these perceptual distortions may have occurred, there is no evidence for the last claim: changing perceived speed. Here we show that dazzle patterns can distort speed perception, and that this effect is greatest at high speeds. The effect should obtain in predators launching ballistic attacks against rapidly moving prey, or modern, low-tech battlefields where handheld weapons are fired from short ranges against moving vehicles. In the latter case, we demonstrate that in a typical situation involving an RPG7 attack on a Land Rover the reduction in perceived speed is sufficient to make the grenade miss where it was aimed by about a metre, which could be the difference between survival or not for the occupants of the vehicle.